Perfusion Changes in Perforator-Based Propeller Flaps - Bernuth, Silvia; Vater, Adrian; Fuchs, Konrad F.; Meffert, Rainer H.; Jakubietz, Rafael G. (Journal of Reconstructive Microsurgery Open, 2023)
Background To cover soft tissue defects, the perforator-based propeller flap offers the option to rotate healthy tissue into complex wounds. By rotating the flap, the perforator is torqued. As a result, perfusion changes are possible.Methods A retrospective data analysis of patients was done, who received a propeller flap to cover soft tissue defects of the lower extremity as well as a peri- and postoperative perfusion monitoring with a laser-Doppler-spectrophotometry system. Additionally, patient-specific data were collected.Results Seven patients were identified. Four patients experienced early complications, two epidermolysis of the distal flap areas, three wound healing disorders, and one partial flap necrosis. Intraoperative perfusion monitoring showed a decline of blood flow after incision of the flap, especially at distal flap site. In case of complications, there were prolonged blood flow declines up to the first postoperative day.Conclusion Torqueing the perforator by rotating the flap can cause an impairment in inflow and outflow. If the impairment is prolonged, perfusion-associated complications are possible. The identification of a viable perforator is particularly important. In addition, a conservative postoperative mobilization is necessary to compensate for the impaired and adapting outflow.
Keywords: propeller flap; perfusion; lower extremity